MINIMALLY INVASIVE SURGERY: A PROMISING APPROACH IN BREAST CANCER TREATMENT (International Seven Journal of Multidisciplinary, 2024)
Minimally invasive surgery (MIS) has emerged as a groundbreaking approach in the treatment of breast cancer, offering numerous benefits over traditional surgical methods. This technique combines advanced technologies and breast preservation strategies, enabling more precise and less traumatic procedures for patients. By minimizing physical and psychological impact, MIS promotes faster recovery times and enhances the overall quality of life for patients. Recent studies highlight the effectiveness of MIS, particularly for early-stage breast cancer. Procedures such as breast-conserving surgery, which may include lumpectomy or the use of minimally invasive tools like high-intensity focused ultrasound (HIFU) or radiofrequency ablation (RFA), offer an attractive alternative to more invasive treatments like mastectomy. These techniques are especially valuable for managing patients' aesthetic concerns and emotional expectations, as they reduce scarring and preserve the breast's natural appearance. Moreover, MIS generally leads to shorter hospital stays, reduced post-operative pain, and lower complication rates. Despite these advantages, the choice of surgical method must be tailored to each patient, taking into account the specific characteristics of the tumor, the patient's health status, and personal preferences. While MIS is not suitable for all cases, it presents a highly effective option for many patients with early-stage breast cancer, providing excellent clinical and cosmetic outcomes. Looking ahead, ongoing research will continue to refine and expand the use of minimally invasive techniques. As these procedures evolve, it is expected that MIS will play a more central role in breast cancer treatment, providing less invasive, more effective alternatives that significantly improve patient outcomes.